Three‐dimensional Surface Area of the Distal Biceps Enthesis, Relationship to Body Size, Sex, Age and Secular Changes in a 20th Century American Sample. (4th January 2013) - Nolte, M.; Wilczak, C.; Henderson, C. Y.; Alves Cardoso, F.
ABSTRACT This study quantifies the influence of body size, sex, age and birth year (secular changes) on the 3D rugose surface area of the biceps brachii attachment site in a sample of 85 White individuals from the Robert J. Terry Collection. Entheseal surface areas were collected using a NextEngine ™ 3D scanner. Several osteometric measurements of the upper limb were used in the initial analysis to determine which were most suitable for use as a body size proxy. In general, articular dimensions correlate more strongly with biceps entheseal surface area than long bone lengths. The distal articular breadth of the humerus shows the strongest correlation with biceps surface area for men (n = 48, r = 0.504) and women (n = 37, r = 0.646). Men are larger bodied and have larger entheseal surface areas; however, women have larger biceps entheses relative to body size. Although the study sample was limited to individuals between the ages 30 and 49 years, age at death still explains approximately 8% of the variation in enthesis size for women (r = 0.284). Men are unequally distributed by age across birth years, and the results for age and secular change are ambiguous because their effects cannot be separated. Birth year explains about 30% of the variation in female rugose entheseal surface area (r = −0.552). Age and birth year together explain about 34% of the variation in enthesis size for men. Overall, body size is the single most significant variable for both men and women, while the combined effects of age and secular change present a nearly equivalent influence on 3D surface area of the biceps brachii enthesis in this 20th century American sample. Copyright © 2013 John Wiley & Sons, Ltd.